Report of the multi-year expert meeting on investment, innovation and entrepreneurship for productive capacity-building and sustainable development on its first session (UN New YorkUS, 2013)
Addresses the issue of regional integration and foreign direct investment. Analyses the impact of regional integration, including subregional, regional and interregional initiatives, on investment flows and the integrating effects of regional investment clusters. Draws best practice policy lessons, including in relation to regional investment agreements and investment promotion, and related implications for sustainable development.
Includes corrigendum.